The mediating role of psychological vulnerability in the relationship between social media dependence and emotional divorce in women - Yaghobi hasankala, Ghasem; Homayouni, Alireza; Yarahmadi, Yahya; Moradi, Omid (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of this study was to determine the mediating role of psychological vulnerability in the relationship between dependence on social networks and emotional divorce in women. Methods: This study was a correlation of structural equations with a covariance-based approach. The statistical population of the study was all women aged 20 to 40 years who referred to 5 counseling centers in cooperation with the Department of Justice in Babol to receive divorce-related services. Taking into account the possibility of incomplete questionnaires, 432 people were selected as purposive sampling. To collect information, questionnaires of social network dependence (2016), psychological vulnerability of carpenters and Davoodi (2001), and emotional divorce of Mohammadi et al. (2015) were used. Results: The results showed that there is a positive and significant relationship between psychological vulnerability and dependence on social networks with emotional divorce (P = 0.05). The indirect path of dependence on social networks was significant with the rate of emotional divorce mediated by psychological vulnerability and the fit of the research model was confirmed (P = 0.05). Conclusion: According to the present study, it is suggested that in terms of mental health as well as the strength of couples’ relationships, counseling and providing appropriate information and education for families in the field of marital improvement and satisfaction should be considered.